Genetic and epigenetic characterization of low-grade gliomas reveals frequent methylation of the MLH3 gene - Lhotska, Halka; Zemanova, Zuzana; Cechova, Hana; Ransdorfova, Sarka; Lizcova, Libuse; Kramar, Filip; Krejcik, Zdenek; Svobodova, Karla; Bystricka, Dagmar; Hrabal, Petr; Dohnalova, Alena; Michalova, Kyra (Genes, chromosomes & cancer, 2015)
Diffuse astrocytomas and oligodendrogliomas (WHO grade II) are the most common histological subtypes of low-grade gliomas (LGGs). Several molecular and epigenetic markers have been identified that predict tumor progression. Our aim was in detail to investigate the genetic and epigenetic background of LGGs and to identify new markers that might play a role in tumor behavior. Twenty-three patients with oligodendroglioma or oligoastrocytoma (LGO) and 22 patients with diffuse astrocytoma (LGA) were investigated using several molecular-cytogenetic and molecular methods to assess their copy number variations, mutational status and level of promoter methylation. The most frequent findings were a 1p/19q codeletion in 83% of LGO and copy-neutral loss of heterozygosity (CN-LOH) of 17p in 72% of LGA. Somatic mutations in the isocitrate dehydrogenase 1 or 2 (IDH1/IDH2) genes were detected in 96% of LGO and 91% of LGA. The O-6-methylguanine-DNA-methyltransferase (MGMT) promoter was methylated in 83% of LGO and 59% of LGA. MutL homolog 3 (MLH3) promoter methylation was observed in 61% of LGO and 27% of LGA. Methylation of the MGMT promoter, 1p/19q codeletion, mutated IDH1, and CN-LOH of 17p were the most frequent genetic aberrations in LGGs. The findings were more diverse in LGA than in LGO. To the best of our knowledge, this is the first time description of methylation of the MLH3 gene promoter in LGGs. Further studies are required to determine the role of the methylated MLH3 promoter and the other aberrations detected.
Keywords: Male; lidé středního věku; Astrocytoma; metylace DNA; epigeneze genetická; Epigenesis, Genetic; Cohort Studies; nádorové biomarkery; MutL Proteins; Humans; astrocytom; Middle Aged; Biomarkers, Tumor; prognóza; mužské pohlaví; Prognosis; Female; Carrier Proteins; kohortové studie; MutL proteiny; ženské pohlaví; DNA Methylation; Neoplasm Grading; Oligodendroglioma; Brain Neoplasms; stupeň nádoru; transportní proteiny; nádory mozku; lidé; oligodendrogliom